2014
DOI: 10.1121/1.4898422
|View full text |Cite
|
Sign up to set email alerts
|

The influence of distance between microbubbles on the fluid flow produced during ultrasound exposure

Abstract: The collapse dynamics of lipid monolayer-coated microbubbles in the clinically-relevant size range under 6 μm in diameter have not been studied directly due to their small size obscuring the collapse visualization. This study investigates the influence of inter-microbubble distance on the shape of lipid debris clouds created by the collapse of the microbubble destroying the microbubble lipid monolayer. The shape was highly influenced by the fluid motion that occurred as the microbubbles collapsed. It was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Microbubbles were extracted from the vial with a 20G syringe needle and then diluted in 0.9% saline. Microbubbles were diluted such that they were well spaced within the channel, at least 100 µm between bubbles to reduce coupling ( Schutt et al 2014 ). This was achieved at a concentration of approximately 10 6 microbubbles/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Microbubbles were extracted from the vial with a 20G syringe needle and then diluted in 0.9% saline. Microbubbles were diluted such that they were well spaced within the channel, at least 100 µm between bubbles to reduce coupling ( Schutt et al 2014 ). This was achieved at a concentration of approximately 10 6 microbubbles/mL.…”
Section: Methodsmentioning
confidence: 99%
“…[184,185] Generated mechanical effects of relevance to delivery include acoustic cavitation, which is the forced size oscillation or growth and collapse of gas microbubbles within a fluid, [186] as well as related fluid streaming. [187][188][189][190] Ultrasound waves penetrate readily through biological tissue and tissue-like constructs and can be applied in a focused manner, [191,192] allowing for in situ manipulation of materials and cells deep within. By controlling the intensity and duration of the applied energy, ultrasound can be employed with high biocompatibility.…”
Section: Ultrasound Activationmentioning
confidence: 99%
“…The ultrasound pulses used here had a peak negative pressure of 0.8 MPa and inertial cavitation has been shown to occur with microbubbles at ultrasound peak negative pressures as low as 0.6 MPa [40]. Passive acoustic detection has confirmed that microbubble inertial cavitation occurs in this experimental setup under these conditions [41]. If inertial cavitation did occur with the 1-3 μm diameter microbubbles, the resulting shockwaves and intense fluid flow could explain the observed large distances over which liposomes were removed and the partial cell detachments.…”
Section: Discussionmentioning
confidence: 58%